USING STORIES IN TEACHING ENGLISH - Khaleel, Mousa (International Journal of Psychosocial Rehabilitation, 2020)
English plays an important role in every part of the world. English is omnipresent in every sector and every walk of life. The young learners should be shown the importance and the interest of learning English for their better future. In schools teachers give much importance to vocabulary, grammar, pronunciation and try to cover their portions for the examination. Young learners are fond of listening to tales and stories and this researcher firmly believe that stories help young learners to learn the language successfully. This paper will focus on the importance of using stories by conducting various activities among young learners in the language learning process.